Attitudes towards physician–nurse collaboration in a primary care team-based setting: Survey-based research conducted in the chronic care units of the Tuscany region of Italy. Issue 1 (2nd January 2016) - Vegesna, Ashok; Coschignano, Christina; Hegarty, Sarah E.; Karagiannis, Tom; Polenzani, Loretta; Messina, Emanuele; Zoli, Romeo; Maio, Vittorio
ABSTRACT: Across the world, multidisciplinary teamwork has become an essential component in the care of patients with chronic conditions—the Chronic Care Units (CCUs) in the Italian region of Tuscany are no exception to this new era of collaboration. We sought to explore the attitudes towards collaboration of general practitioners (GPs) and nurses within the CCUs using the Jefferson Scale of Attitudes towards Physician–Nurse Collaboration (JSAPNC). The survey was sent electronically to 218 GPs and 46 nurses of 23 CCUs in two Local Health Authorities of Tuscany. A higher JSAPNC score is indicative of a more positive attitude towards physician–nurse collaboration. JSAPNC scores were calculated for both totals and by three factors: "shared education and collaboration, " "caring versus curing, " and "physician authority." A total of 133 healthcare professionals (94 GPs and 39 nurses) responded (response rate = 51.5%). Nurses reported significantly more positive attitudes towards collaboration than GPs (52.5 vs. 44.0, p < 0.01). This trend was also found in each of the three factors. This information adds to the scarce literature on nurse–physician collaboration in the primary care setting and highlights the need for considerable improvement given the rise of team-based outpatient care models.